The impact of infrastructure spending on economic growth of the Philippines - David, Aries May G.; Rivera, Shienna R. (Pampanga University of the Philippines Diliman Extension Program in Pampanga, 2006)
Infrastructure investments in roads and bridges, telecommunications, water supply and irrigation have a significant impact on economic activities of the country. It provides valuable services to firms and individuals. The availability of an adequate infrastructure is, therefore, necessary for the efficient functioning of the other sectors of the economy and for the attainment of the respective development goals. This study seeks to find how infrastructure investments affect the economic growth of the Philippines. In the absence of statistical records on the infrastructure spending, we will limit our study from 1986-2004. Secondary data were gathered through books, papers and documents produced by the government. The result of the study has described the state of infrastructure investment of the country for the 19-year period. The relationship of infrastructure spending to Gross Domestic Product and its effect on the growth of the economy were also identified. It was found out that infrastructure investment in the country is low, thus it deserves special attention. In spite of the fact that the government invests in infrastructure, still, it is not enough to address the high demand of individuals and firms for infrastructure facilities and services. In effect, private sectors will step in and will finance the budget required for infrastructure expenditures. Improving the infrastructure of the country may result to high level of productivity that results to economic growth.
Thesis (Business Economics) UPDEPP, 2006
Keywords: Infrastructure (Economics) -- Philippines